Cyclodextrin derivatives as mimics of enzymes and antibodies - Ronald Breslow (ՀՀ ԳԱԱ հրատ.)
The cyclodextrin derivatives as enzyme mimics and imitators of antigens binding by antibodies are reviewed.
Keywords: Biology; Biochemistry